The Fintech sector in Latvia: Opportunities, Risks and Challenges for national development - Leonardo Pataccini (ResearchGate, 2023)
In recent years, the development of new financial technologies, or Fintech, has been regarded as one of the most disruptive and relevant phenomena not only for the financial sector but for the overall economy. However, to date, most of the research on Fintech has focused on the opportunities and risks for firms and there is little research on the implications of Fintech for the development of national economies. Therefore, the current report aims to provide a critical assessment of the potential role of the expansion of the Fintech sector for Latvia. In doing so, the report answers the following question: How does the Fintech sector fit into Latvia's development strategy and what are its implications? The report finds that, in its current form, the Fintech sector can be a useful means of facilitating development and innovation, but hardly a driver of development in itself. As policy recommendations, the report highlights the need to build regulatory expertise. The evidence shows that the risks posed by the Fintech sector are quantitatively and qualitatively different from those of traditional finance. Therefore, in order to contain risks and maximize benefits, a more proactive and tailored regulatory approach is required.
Keywords: G2; G3; 330; Fintech; Latvia; Development; Baltic states; Finance; Central Bank digital currencies; Financial Risk; Climate and Finance